A thin-film silicon based photocathode with a hydrogen doped TiO2 protection layer for solar hydrogen evolution. Issue 43 (20th October 2016) - Liang, Junhui; Tan, Hairen; Liu, Min; Liu, Bofei; Wang, Ning; Zhang, Qixing; Zhao, Ying; Smets, Arno H. M.; Zeman, Miro; Zhang, Xiaodan
Abstract : There is a trade-off relationship between activity and stability in silicon based monolithic photovoltaic electrochemical (PV–EC) systems, especially when a thick TiO2 protection layer (preferred to enhance the chemical stability in the electrolyte) is used. Abstract : Photoelectrochemical (PEC) devices for solar water splitting require not only high solar to hydrogen conversion efficiency but also high chemical stability in strong acidic or alkaline electrolytes for long-term operation. Titanium dioxide (TiO2 ) has been considered as a highly promising protection layer to achieve high chemical stability for solar water splitting devices, especially for silicon based monolithic photovoltaic electrochemical (PV–EC) systems, while there is a trade-off relationship between activity and stability in these devices: the high charge transport barrier at the PV (silicon based thin film solar cells)/TiO2 interface and the high ohmic loss in TiO2 films hinder the device performance, especially when a thick TiO2 protection layer (preferred to enhance the chemical stability in the electrolyte) is used. Herein, we show that a hydrogen doped TiO2 protection layer can break this traditional trend to increase the activity without deteriorating the stability, when thick protection layers are employed to ensure stability. We demonstrated significant performance enhancement in hydrogenated amorphous silicon/silicon germanium (a-Si:H/a-SiGe:H) photocathodes through this approach. On one hand, the H-doping can shift up the Fermi level and reduce the electron transport barrier at the interface of the PV/TiO2 protection layer. On the other hand, the higher carrier density via H-doping leads to the enhancement of electron transport in TiO2 films and a shorter depletion layer barrier. Thus, the H-doping results in a higher photocurrent output at 0 V vs. reversible hydrogen electrode (RHE), indicating the high potential of the H-doped TiO2 protection layer for achieving stable and efficient monolithic solar water splitting devices.